Addressing the Enforcement Gap to Counter Crime : Part 1. Crime, Poverty and the Police - Gramckow, Heike P.; Greene, Jack; Marshall, Ineke; Barao, Lisa (World Bank, Washington, DC, 2016)
Crime and violence impede development and disproportionally impact poor people in many countries across the world. Though crime and violence represent serious problems in many countries, less-developed countries experience particular concentrations, especially those that are characterized by fragile or less-trusted government institutions and pervasive insecurity. Under such circumstances, human, social, political, and economic development suffers. Research across the globe has shown that holistic approaches that focus on the entire spectrum of a government's crime response chain, ranging from crime prevention to enforcement, tend to have better outcomes than isolated interventions involving only the police or other individual government agency. To date, most of the Bank's investment in efforts to reduce crime have focused on crime prevention in the form of urban and social development programs. Investment and policy lending that support the improvement of police operations to reduce crime and develop stronger neighborhoods are more limited. To assist country teams and client counterparts in their efforts to develop effective, holistic responses against crime that include the police, justice reform staff in the Governance Global Practice teamed up with internationally recognized experts to compile evidence-based good practice information for developing effective police responses to crime. The resulting three part publication, titled Addressing the Enforcement Gap to Counter Crime: Investing in Public Safety, the Rule of Law and Local Development in Poor Neighborhoods outlines the impact of crime and violence on development and the poor in particular and explains a proven three-pronged approach to creating police agencies that work in collaboration with communities and other government and private service providers to identify crime problems, develop holistic and inclusive solutions the apply a restorative justice approach. The publication also outlines how such approach can be integrated into Bank projects and client country reform plans.